Pemikiran Pendidikan Holistik Said Nursi: Integrasi antara Ilmu, Akhlak, dan Spiritualitas dalam Pengembangan Pendidikan Islam - Rasmuin Rasmuin (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
This article discusses the holistic educational thought of Said Nursi, who is a well-known Islamic thinker and educator in the 20th century. Nursi's holistic educational thinking integrates three important aspects in the development of Islamic education, namely knowledge, morals, and spirituality. Nursi believes that education must teach true and useful knowledge, while at the same time building good character and morals in individuals. In this case, morals and spirituality are very important to instill in education, because these two things can influence a person's behavior and outlook on life. In addition, Nursi also emphasized the importance of a holistic approach in educational development, in which all aspects of individual life must be considered in the learning process. This is done so that education not only produces academically intelligent individuals, but also has strong character and spiritual abilities. In this article, we will discuss in depth the concept of Nursi's holistic education, including how to develop holistic education and implement Nursi's holistic educational thinking in the context of Islamic education. With this in mind, it is expected to help the development of better and holistic Islamic education, which not only produces academically intelligent individuals, but also has character and ability.